2002
DOI: 10.1046/j.1525-142x.2002.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

The development and evolution of insect mouthparts as revealed by the expression patterns of gnathocephalic genes

Abstract: To understand better both the development and evolution of insect mouthparts, we have compared the expression pattern of several developmentally important genes in insects with either mandibulate or stylate-haustellate mouthparts. Specifically, we examined the expression of the proboscipedia (pb) and Distal-less (Dll) gene products as well as three regulators of pb, Sex combs reduced (Scr), Deformed (Dfd), and cap 'n' collar (cnc). These genes are known to control the identity of cells in the gnathal segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 41 publications
1
72
0
2
Order By: Relevance
“…Selector genes encode transcription factors that, in combinations, define the body plan by controlling the development of specific regions of the embryo, and have been implicated in the evolution of body plan variations (Averof and Akam, 1995;Carroll et al, 2001;Duboule, 1994;Gellon and McGinnis, 1998;Manak and Scott, 1994;Panganiban et al, 1995;Rogers et al, 2002;Warren et al, 1994). In insects, selector genes are thought to modify the development of a default, or 'ground state', appendage into a tagma-specific appendage such as a mouthpart, antenna or leg.…”
Section: Introductionmentioning
confidence: 99%
“…Selector genes encode transcription factors that, in combinations, define the body plan by controlling the development of specific regions of the embryo, and have been implicated in the evolution of body plan variations (Averof and Akam, 1995;Carroll et al, 2001;Duboule, 1994;Gellon and McGinnis, 1998;Manak and Scott, 1994;Panganiban et al, 1995;Rogers et al, 2002;Warren et al, 1994). In insects, selector genes are thought to modify the development of a default, or 'ground state', appendage into a tagma-specific appendage such as a mouthpart, antenna or leg.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, both mRNA expression and functional analyses in Oncopeltus (Hughes and Kaufman, 2000;Rogers et al, 1997;Rogers et al, 2002) have shown that Scr governs the formation of the sex combs on the distal tibia of the T1 leg (Fig. 3F inset, top).…”
Section: Scr Patterning In the T1 Leg Is Very Dynamic And Characterizmentioning
confidence: 93%
“…Numerous studies have shown that changes in the expression and function of homeotic (hox) genes were pivotal in the evolution of the insect bauplan (Beeman et al, 1993;Beeman et al, 1989;Carroll et al, 2001;Hughes and Kaufman, 2000;Hughes and Kaufman, 2002;Mahfooz et al, 2007;Mahfooz et al, 2004;Rogers et al, 1997;Rogers et al, 2002;Struhl, 1982;Tomoyasu et al, 2005). This insight was primarily based on mRNA expression patterns, however, data on protein accumulation are much more limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we test the hypothesis that the main axis of the adult maxillary and labial appendages is patterned using genes also required in the leg development network. Key aspects of this network are conserved in the legs of numerous arthropods, suggesting that they were likely components of the leg patterning network of ancestral arthropods (e.g., Palopoli and Patel 1998;Abzhanov and Kaufman 2000;Jockusch et al 2000;Beermann et al 2001;Schoppmeier and Damen 2001;Inoue et al 2002;Rogers et al 2002;Angelini and Kaufman 2005b;Prpic and Damen 2009;Angelini et al 2012). Second, we test several hypotheses about the mechanism that governs branching of the PD axis to give rise to endites.…”
mentioning
confidence: 97%